Correction: Selim et al. Impact of Washingtonia robusta Leaves on Gamma Irradiation-Induced Hepatotoxicity in Rats and Correlation with STING Pathway and Phenolic Composition. Pharmaceuticals 2020, 13, 320 - Nabil M. Selim; Seham S. El-Hawary; Soheir M. El Zalabani; Rehab Nabil Shamma; Nariman El Sayed Mahdy; Noheir H. Sherif; Hanan A. Fahmy; Mai H. Mekkawy; Abdelaziz Yasri; Mansour Sobeh (Pharmaceuticals)
In the original publication [...]